Pemberdayaan Masyarakat Melalui Inovasi Pengolahan Gambir Menjadi Teh Herbal Bernilai Ekonomi - Zalisman, Zalisman; Purnamasari S, Ayu; Abidin, Zaitun; Apryani Simbolon, Indah; Nasution, Balyan; Junisa Putri, Lala (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2024)
This community service activity was carried out in Nagari Durian Tinggi, West Sumatra, with the aim of empowering the community through the innovation of processing gambier into economically valuable herbal tea. Until now, gambier has mostly been sold in raw form at a relatively low price. In fact, gambier contains bioactive compounds such as catechins and tannins that are beneficial for health, making it highly potential to be developed into herbal drink products. The method applied in this activity was Participatory Action Research (PAR), which actively involved lecturers, students, and the local community in the stages of planning, implementation, and evaluation. The program was conducted through counseling, discussions, and hands-on practice of processing gambier into herbal tea, including raw material selection, processing, drying, and packaging. The results showed an increase in participants’ knowledge, skills, and awareness regarding the diversification of gambier products. Participants were able to produce simple herbal tea products with higher economic value compared to raw gambier. Therefore, this innovation is expected to improve community welfare, strengthen local economic independence, and encourage the development of sustainable, locally based businesses